Supporting Preschool Children’s Resilience at Basic Daily Context: Parents’ and Teachers’ Views in Selected Kindergartens in Greece - , Karela Christina (Archives of Current Research International, 2024)
Aims: This paper aimed to shed light on the understanding of the concept of ‘risk and resilience’ by young children’s main caregivers (parents and kindergarten teachers), as well as to explore and compare their perspectives on the daily applied strategies to develop and promote children’s resilience at home and school respectively. Study Design: A qualitative approach was chosen in order to evaluate parents’ and kindergarten teachers’ beliefs, experiences and attitudes towards ‘resilience’ through semi-structured interviews. Place and Duration of Study: The study conducted in Greece and the whole procedure from design to data analysis and report writing lasted eight months (from January to August 2023). Methodology: 17 mothers of preschool children (3.5 to 5.5 years old) and 16 kindergarten teachers who worked in public kindergartens from different regions in Greece participated in the study, selected by a convenience sampling. Thematic analysis was used to analyze the qualitative data from the participants’ responses to the interviews. Results: Mothers and kindergarten teachers recognized risk and stressors in children development. Their discrepancy was that teachers emphasized the importance of risk factors in the family such as neglect, abuse, divorce, financial problems etc., while mothers referred more to child individual (e.g. disease, cognitive disability) or socio-cultural factors (e.g. crisis, bulling, internet addiction). They both seemed adequate enough to capture the essential features of the concept ‘resilience’ such us “positive adaptation after a threat or adversity”. As concerned the strategies to support children’s resilience both kindergarten teachers and mothers considered that they could serve as positive role models for promoting resilience. They put first their relationship/ bonding with the child as well as the interactions between the two contexts (family-school). They adopted appropriate practices (e.g. discussion, story reading, social scenarios, expression support) to achieve their goals mainly related to socio-emotional learning/ development. Conclusion: The conclusions were hoped to have major implications for parents and teachers, suggesting that they can be used for the design of training or intervention programs focusing in enhancing children’s resilience and to guide principles and policy decisions that influence the field of early education.